2015
DOI: 10.1074/jbc.m114.592261
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-independent Phospholipase A2γ Enhances Activation of the ATF6 Transcription Factor during Endoplasmic Reticulum Stress

Abstract: Background: Calcium-independent PLA 2 ␥ (iPLA 2 ␥) is a membrane-bound enzyme that localizes at the endoplasmic reticulum (ER). Results: iPLA 2 ␥ amplified activation of the ATF6 pathway of the unfolded protein response, resulting in up-regulation of ER chaperones and cytoprotection. Conclusion: iPLA 2 ␥ enhances activation of ATF6. Significance: Modulating iPLA 2 ␥ activity may provide opportunities for pharmacological intervention in glomerular diseases associated with ER stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 42 publications
0
35
1
Order By: Relevance
“…Stimulation of iPLA 2 ␥ was dependent on phosphorylation of Ser-511 and/or Ser-515 via MNK1 (MAPK-interacting kinase 1) (20). In addition to characterizing these signaling pathways, we showed that overexpression of iPLA 2 ␥ in cultured GECs reduced complement-mediated GEC injury (19) as well as injury by tunicamycin, which was associated with augmentation of the ATF6 (activating transcription factor 6) pathway of the unfolded protein response in the ER (21). In other cells, such as primary cultures of rabbit renal proximal tubules cells, knockdown of iPLA 2 ␥ expression increased lipid peroxidation and impaired mitochondrial function (22).…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…Stimulation of iPLA 2 ␥ was dependent on phosphorylation of Ser-511 and/or Ser-515 via MNK1 (MAPK-interacting kinase 1) (20). In addition to characterizing these signaling pathways, we showed that overexpression of iPLA 2 ␥ in cultured GECs reduced complement-mediated GEC injury (19) as well as injury by tunicamycin, which was associated with augmentation of the ATF6 (activating transcription factor 6) pathway of the unfolded protein response in the ER (21). In other cells, such as primary cultures of rabbit renal proximal tubules cells, knockdown of iPLA 2 ␥ expression increased lipid peroxidation and impaired mitochondrial function (22).…”
mentioning
confidence: 91%
“…The detailed method and characterization of the cells was published previously (21). Briefly, by quantitative reverse polymerase chain reaction, iPLA 2 ␥ mRNA was present in cells derived from WT mice but was completely absent in cells from KO mice.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations